EPEN-04. RECURRENT EPENDYMOMA: ROLE OF INTRAVENTRICULAR TARGETED RADIOIMMUNOTHERAPY. Issue 2 (22nd June 2018) - Kramer, Kim; Taskar, Neeta Pandit; Humm, John; Zanzonico, Pat; Donzelli, Maria; Haque, Sofia; Khakoo, Yasmin; Lewis, Jason; Cheung, Nai-Kong
Abstract: PURPOSE: Novel treatment strategies are needed for children with recurrent ependymoma. We explored the use of intraventricular targeted immunotherapy with monoclonal antibodies (cRIT-mAb) using 131 I-8H9 and 131 I-3F8 targeting B7-H3 or GD2, respectively. METHODS: Patients received 2 mCi cRIT- 131 I- mAb for dosimetry with serial CSF sampling and region of interest (ROI) on nuclear scans. Therapy injections were 40 -100 mCi 131 I-8H9 or up to 40 mCi 131 I-3F8. Brain and spine MRIs, CSF cytology were routinely assessed. Acute toxicities and survival were noted. RESULTS: 11 patients with anaplastic ependymoma (median age 8.5 years, 1–32) suffered 1- 7 recurrences (median 2.9); median age at cRIT was 12.3 years (3–35). 39 injections were delivered (13 131 I-3F8; 26 131 I-8H9). Transient headache, nausea and vomiting was observed following 131 I-3F8; 131 I-8H9 was well-tolerated. Mean CSF cGy/mCi by sampling was 37.6 131 I-8H9 and 40.1 131 I-3F8. Mean ventricular ROI dose was 75.3 cGy/mCi 131 I-8H9 and 111 cGy/mCi 131 I-3F8 and to spine 20.2 cGy/mCi 131 I-8H9 and 18.9 cGy/mCi 131 I-3F8. 4/5 patients with radiographic evidence of disease progressed; 1 had spinal disease improvement. Of 5 patients treated in radiographic remission, 2 remain in remission 2.5 and 8 years since cRIT, 1 is alive with disease 2.5 years post; 2 patients died of disease 7 and 13 years post cRIT. CONCLUSIONS: cRIT mAb appear safe with a favorable dosimetry therapeutic index and may be considered as a viable therapeutic option for patients with recurrent ependymoma.